Analisis Mahasiswa KKN Terhadap Peningkatan Kemampuan Membaca & Menghafal Al-Quran Anak TPA/TPQ - Rahim, Bulkia; Syaryani, Riska Nava; Reza Nurrahmi Putri; Angelique, Aisyah Farahin; Cristin, Cristin; Ammy, Rahmad Isrok (J-CoSE: Journal of Community Service & Empowerment, 2024)
Kuliah Kerja Nyata (KKN) is a student's vessel in the application of science that has been obtained in lectures to apply to society.Student devotion needs to see the problems that society is facing then solves innovatively.Helping educators in society is one of the things that can be done, By focusing on guiding the addition of the students memorabilia in TPA/TPQ Mushala Al-Muhklisin, Kelurahan Bungus Barat, Kecamatan Teluk Kabung, Kota Padang. The subject of research is the entire protege in TPA/TPQ Mushala Al-Muhklisin.This research uses descriptive methods with a qualitative approach that aims to describe the al-Qur'an read and memorized methods that have been applied.The results of activities show an increased child's ability after giving a motivation or giving a meaning to the final goal of a disciple need to add to their memorization.